Management of tacrolimus‐associated food allergy after liver transplantation. Issue 6 (5th November 2015) - Obayashi, Naho; Suzuki, Mitsuyoshi; Yokokura, Tomoaki; Naritaka, Nakayuki; Nakano, Satoshi; Ohtsuka, Yoshikazu; Sugo, Hiroyuki; Kawasaki, Seiji; Shimizu, Toshiaki
Abstract: Increasingly, food allergy associated with tacrolimus after pediatric living‐donor liver transplantation (LT) has been reported. Tacrolimus prevents the activation of T cells by blocking calcineurin, thus producing an immunosuppressive effect, but tacrolimus induces an imbalance in T‐helper type 1 (Th1) and Th2 cells in the food allergy process. This report describes a case of tacrolimus‐associated food allergy after pediatric living‐donor LT. The patient was a 7‐year‐old Japanese girl who had undergone living‐donor LT at 12 months of age, and whom we first saw in the clinic at age 18 months. She received immunosuppressive therapy by tacrolimus after transplantation. Atopic dermatitis developed in post‐transplant month 18. Stridor, facial edema, lip swelling, and skin erythema after consuming tempura udon containing wheat occurred in post‐transplant month 39, and she was subsequently diagnosed with anaphylactic shock. Eosinophilic leukocyte and serum immunoglobulin (Ig)E increased, and specific IgE was positive for some food allergens. Pharmacotherapy was therefore changed from tacrolimus to cyclosporine A, after which eosinophilic leukocyte and serum IgE decreased and atopic dermatitis improved.